Early Investment Fraud Detection Training for Mother Community (Empowerment and Family Welfare Mobilization of Banjarejo Village) - Qimyatussa’adah Qimyatussa’adah; Rosida Ibrahim; Nika Esti Rahayu; Yana Dwi Christanti; Hedi Pandowo (Journal of Community Engagement, 2025)
Fraudulent investment schemes have become increasingly common, particularly targeting individuals with low financial literacy, such as housewives who manage household finances but often lack financial education. This community-based training, conducted with the Banjarejo Village Empowerment and Family Welfaregroup, used real case examples, participatory learning, and visual media to facilitate early detection skills. The one-day training involved 20 participants and resulted in significant improvement in understanding red flags of fraudulent investments. Post-training evaluations showed 85% of participants could correctly identify indicators of illegal schemes, and 70% committed to disseminating the knowledge in their communities. This initiative highlights the strategic role of mothers in financial literacy dissemination. Community-focused, practical training is effective in reducing vulnerability to investment fraud.